In vitro degradation of Poly-L-co-D, L-lactic acid membranes - Baraúna,Grazielle (2013)
Poly-L-co-D.L-lactic (PLDLA) is a bioresorbable polymer whose properties have been studied for degradation sensitivity and its application in medicine. In this study, the potential of PLDLA membranes for temporary implantation was evaluated. PLDLA membranes were prepared with the solvent evaporation technique and characterized by differential scanning calorimetry, gel permeation chromatography, thermogravimetric analysis, scanning electron microscopy and traction tests. The glass transition temperature of the membranes was 59 ºC. Degradation started around 340 ºC during the second week showing pores and fissures on the broken surface. Evident degradation was observed after 16 weeks. Microscopy showed that before degradation PLDLA membranes presented no pores. PLDLA properties of resistance to traction and elasticity module were maintained until the 8th week, and after the 16th week there was a sharp reduction of these properties due to degradation. PLDLA membranes present excellent potential as temporary implantation given their degradation characteristics.